SIKAP TERHADAP SAINS SISWA DALAM PEMBELAJARAN FISIKA MELALUI PENERAPAN STRATEGI METAKOGNITIF DI KELAS X SMA IT AL-ITTIHAD PEKANBARU - Sartika, Venny Sartika; ', Zulhelmi; ', Azizahwati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to determine the increase  student’s attitude toward science in learning physics at class X SMA IT Al-Ittihad Pekanbaru through the implementation of Metacognitive Strategies in lesson temperature and heat. The subjects were students of class X Putri totalling 18 students. The metodh used in this study is pre-experimental with one group pretest-posttest desigs. The instrument of data collection in this study is the attitudes towards science questionnaire consists of 24 statement that include 4 attitude toward science indicator which is attraction toward science, science learning activities, importance of science, views toward science’s environmental. Data analysis in this study is a descriptive analysis to determine the increase  student’s attitude toward science in learning physics. The research showed the gain student’s attitude toward science at class X SMA IT Al-Ittihad Pekanbaru through the implementation of Metacognitive Strategies in lesson temperature and heat are in middle category (0,42), increase of the student’s attitude toward science in each of indicators in middle category, except importance of science in low category. Key Words : Metacognitive Strategies, Attitude toward science